MODEL PENINGKATAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR BERBASIS MOTIVASI INTRINSIK DAN ORGANIZATIONAL JUSTICE PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PONOROGO - Yuniarko, Dhevit; Suwardi, Suwardi; Winarni, Liliek (JI@P, 2020)
The problem of decreasing absenteeism towards the performance of the State Civil Apparatus (ASN) caused by declining intrinsic motivation originating from himself and organizational justice is still an interesting thing to study. This study aims to determine the Model of Improvement of Organizational Citizenship Behavior Based on Intrinsic Motivation and Organizational Justice in the Population and Civil Registration Office of Ponorogo Regency. This research was conducted at the Population and Civil Registry Office of Ponorogo Regency and the data obtained through a questionnaire along with an interview guide distributed to 42 respondents and analyzed using Path Analysis. Based on the results of the study, it can be concluded that the increase in Organizational Citizenship Behavior can be done by increasing Intrinsic Motivation and Organizational Justice by being mediated by Affective Commitments. Intrinsic motivation and good organizational justice will encourage increased affective commitment which will ultimately improve employee performance through Organizational Citizenship Behavior. Employees who always have high intrinsic motivation will have high performance. The more employees feel they get organizational justice in an organization that is able to absorb, understand and implement it, the higher the employee's performance. The limitation of this study raises suggestions for future research, namely the need for appropriate moderation variables to encourage the strengthening of the influence of variables on performance.